Pengaruh Corporate Governance Terhadap Income Smoothing Dengan Intellectual Capital Disclosure Sebagai Variabel Mediasi Pada Perusahaan Yang Terdaftar Dalam BEI - Irene Melina Teguh; Saarce Elsye Hatane (Business Accounting Review, 2017)
The purpose of this study was to know the direct affect of the corporate governance toward income smoothing. This study also wanted to know the indirect affect of corporate governance toward income smoothing with intellectual capital disclosure as a mediation variable. This study used quantitative method by using secondary data such as annual report and financial report. The sample of this study is 72 manufacturing companies that were listed in Indonesian Stock Exchange from 2010-2015. The data analysis method was tested by using partial least square (PLS) with the Warp PLS 5.0 program. The result of this study revealed that corporate governance had no significant affect on income smoothing, but indirectly affected through intellectual capital disclosure as a mediation variable.